Dynamic Contrast‐Enhanced Perfusion MRI of High Grade Brain Gliomas Obtained with Arterial or Venous Waveform Input Function. Issue 1 (29th April 2015) - Filice, Silvano; Crisi, Girolamo
ABSTRACT: BACKGROUND AND PURPOSE: The aim of this study was to evaluate the differences in dynamic contrast‐enhanced (DCE) magnetic resonance imaging (MRI) perfusion estimates of high‐grade brain gliomas (HGG) due to the use of an input function (IF) obtained respectively from arterial (AIF) and venous (VIF) approaches by two different commercially available software applications. METHODS: This prospective study includes 20 patients with pathologically confirmed diagnosis of high‐grade gliomas. The data source was processed by using two DCE dedicated commercial packages, both based on the extended Toft model, but the first customized to obtain input function from arterial measurement and the second from sagittal sinus sampling. The quantitative parametric perfusion maps estimated from the two software packages were compared by means of a region of interest (ROI) analysis. The resulting input functions from venous and arterial data were also compared. RESULTS: No significant difference has been found between the perfusion parameters obtained with the two different software packages ( P ‐value < .05). The comparison of the VIFs and AIFs obtained by the two packages showed no statistical differences. CONCLUSIONS: Direct comparison of DCE‐MRI measurements with IF generated by means of arterial or venous waveform led to no statistical difference in quantitative metrics for evaluating HGG. However, additional research involving DCE‐MRI acquisition protocols and post‐processing would be beneficial to further substantiate the effectiveness of venous approach as the IF method compared with arterial‐based IF measurement.